Outcomes of lung transplants utilizing donors from outside the continental United States - Reed T. Jenkins, MD; Emily L. Larson, MD; Alice L. Zhou, MD; Jessica M. Ruck, MD, PHD; David J. Farhat, MD; Helene Rached, DO; Al-Faraaz Kassam, MD, MBA; Christian A. Merlo, MD; Ramon A. Riojas, MD; Errol L. Bush, MD (JHLT Open)
Background: Efforts to expand the lung transplant donor pool have included re-evaluating geographic restrictions and accepting longer distances between donor and recipient centers. We evaluated the use of organs from donors outside the continental United States. Methods: Adult lung-only transplants from 2005-2022 in the United Network for Organ Sharing database were included and categorized based on donor location (mainland US vs nonmainland). Survival out to 1 and 5 years post-transplant was evaluated using time-to-event analysis and multivariable Cox regression. Results: Of 35,638 transplants, 389 (1.1%) utilized nonmainland donors. Nonmainland donors were younger (median 28 vs 33 years, p < 0.001), had lower body mass index (24 [22-27] vs 25 [23-29] kg/m2, p < 0.001), and were less likely to have a >20 pack-year smoking history (4.9% vs 9.1%, p = 0.004). Recipients of nonmainland vs mainland lungs were less likely to have restrictive pathology (57.2% vs 59.5%, p < 0.001) and had lower body mass index (25 [21-28] vs 26 [22-29] kg/m2, p = 0.002). Nonmainland transplants had greater distances between donor and recipient centers (1,256 [1,072-1405] vs 148 miles [29-310], p < 0.001) and longer ischemic times (7.7 [6.9-8.8] vs 5.2 [4.2-6.3] hours, p < 0.001). Transplants utilizing nonmainland and mainland donors had similar post-transplant survival out to 1 (aHR 1.03 [95% CI 0.78-1.35], p = 0.86) and 5 years (aHR 0.87 [95% CI 0.73-1.04], p = 0.13). Conclusions: Transplants utilizing nonmainland donors had lower-risk donor and recipient characteristics. Despite greater distances and ischemic times, these transplants had similar post-transplant survival compared to transplants using mainland donors, supporting the use of select donors from outside the mainland United States.